Use of routine ureteral stents in cesarean hysterectomy for placenta accreta. (1st February 2021) - Crocetto, Felice; Esposito, Rosanna; Saccone, Gabriele; Della Corte, Luigi; Sarno, Laura; Morlando, Maddalena; Maruotti, Giuseppe Maria; Migliorini, Sonia; D'Alessandro, Pietro; Arduino, Bruno; Raffone, Antonio; Travaglino, Antonio; et al.
Abstract: Objective: To evaluate benefits of use of ureteral stents in association with cesarean hysterectomy in case of placenta accreta. Methods: This was a single center, cohort study. Clinical records of singleton pregnancies with placenta accreta who underwent cesarean hysterectomy were included in the study. For this study, pregnancies with diagnoses of placenta accreta, increta, or percreta were considered under the umbrella term of placenta accreta. For all women with placenta accreta, delivery was planned via cesarean hysterectomy at 34 0 –35 6 weeks, without any attempt to remove the placenta. Reasons for earlier delivery included vaginal bleeding and spontaneous onset of labor. The primary outcome was the incidence of unintentional urinary tract injury. Outcomes were compared in a cohort of women who had planned the placement of ureteral stents and in those who did not. Results: Forty-four singleton gestations with confirmed placenta accreta at the time of cesarean hysterectomy were included in the study. Twenty-four (54.5%) of the included women had the placing of ureteral stents prior to cesarean, while 20 (45.5%) did not. At histological confirmation, most of them had placenta accreta (17/44, 38.6%), 14 placenta increta (31.8%), and 13 placenta percreta (29.6%). Urinary tract injuries occurred in eight cases (18.2%), six in the ureteral stents and two in the non-ureteral stents group (25 versus 10%; p  = .21). All the injuries were bladder injuries, while no cases of ureteral injury were recorded. All injuries were recognized intraoperatively. Conclusion: In case of placenta accreta, the use of ureteral stents in association with cesarean hysterectomy does not reduce the risk of urinary tract injury.